UZBEKISTAN AND THE REPUBLIC OF KOREA: FACTORS OF SUSTAINABLE DEVELOPMENT - Tolliboyeva Zarina (PT. Antis International Publisher, 2025)
Objective: This study provides a comprehensive analysis of the evolving bilateral and multilateral relations between the Republic of Korea and Central Asian countries, with a particular focus on Uzbekistan. It examines the multifaceted cooperation in the spheres of economy, politics, migration, security, technology, transportation infrastructure, and cultural exchange. Method: Employing an interdisciplinary approach and comparative analysis, the paper evaluates the current state of diplomatic and strategic engagement, identifies key challenges impeding further progress, and explores future perspectives for enhancing collaboration. Results: The research highlights how Uzbekistan and other Central Asian states increasingly view South Korea as a reliable and technologically advanced partner, whose influence in the Asia-Pacific region makes it a valuable actor in regional development strategies. South Korea’s soft power, developmental assistance, and knowledge-sharing initiatives have further cemented its role in the region. Additionally, the study underscores the importance of institutional frameworks, high-level diplomatic visits, and economic forums that have facilitated dynamic cooperation. Novelty: Ultimately, the paper argues that the deepening ties between South Korea and Central Asia not only promote mutual development but also contribute to regional stability and integration within broader global processes.